(untitled) (Bangladesh Journal of Child Health, 2015)
Background: The development of acute kidney injury (AKI) in critically ill patients, or AKI children worsened to be critically ill, is associated with increased morbidity and mortality. Early detection on AKI improves its poor outcome in those children. To study the incidence and correlate the outcome of critically ill children with AKI in children admitted to Pediatric Intensive Care Unit (PICU) at Dr. Soetomo Hospital Surabaya. Methodology: We prospectively studied children admitted to PICU during 15 January to 14 April 2014. Demographic data including age and sex, PICU indications, and AKI staging were recorded. All data were analyzed by descriptive statistics and chi-square test (P<0.05). Results: A total of 119 children were admitted to PICU during study period. Among those, 63 children were excluded for being <3 months old, had end-stage kidney disease or complex cardiac problem, and children underwent cardiac catheterization. The remaining 56 (47.1%) were studied further, mean age was 49.7 (SD 46.2) months, male-to-female ratio was 1.2:1. Indication for PICU admission was dominated by shock (35.7%), followed by central nervous system (CNS) dysfunction in 13 (23.2%) and respiratory failure in 12 (21.4%) children. AKI was noted in 15 (26.8%) children, mostly (10.7%) in Injury stage with 5 (8.9%) in Risk and 4 (7.1%) in Failure stages. Twelve (21.4%) children died, 7 (58.3%) had AKI with 3 (25.0%) each in Risk and Failure stages while 1 (8.3%) in Injury (P<0.05). Conclusion: The incidence of AKI was moderate in critically ill children but significantly associated with mortality rate. DOI: http://dx.doi.org/10.3329/bjch.v38i3.22818 Bangladesh J Child Health 2014; VOL 38 (3) :120-123